Microbes and microbiomes in 2020 and beyond - Aravind Natarajan (Nature Portfolio, 2020)
In the next decade, advances in our understanding of microbes and microbiomes will likely transform our way of life; providing novel therapeutics, alternate energy sources, and shaping fundamental doctrines of biology. We explore the promises herein, and tools required to achieve this progress. Notably, it is critical that we improve the inclusivity and diversity of our research agendas and teams, so that science benefits people of all identities and backgrounds.